Empowerment of Women through Self-Help Groups in Tiruvannamalai - Leelavathy, Dr. K. (International Journal of Scientific Research and Management (IJSRM), 2014)
Micro- finance through Self Help Groups (SHG) has been recognized internationally as the modern tool to combatpoverty and for rural development. When micro- finance is extended to people, especially women, along withsupporting activities like training, raw materials supply and marketing of products, it makes women as microentrepreneursin rural areas. In addition to empowerment, it results in economic development of the family. The SHGbecomes matured and sustainable when the members, as a team achieve the goals and aspirations. The members areable to face conflicts, challenges and constraints with their courage, confidence and empowerment. For any strategicapproach to be sustainable, it is important to track the deficiencies and constraints for making necessary corrections,adjustments at the policy level and also implementation levels.